Constraints on EOS from finite nuclei, heavy ion collisions and neutron stars - Gaitanos, T.; Ferini, G.; Colonna, M.; Di Toro, M.; Lalazissis, G. A.; Wolter, H. H. (HNPS Advances in Nuclear Physics, 2020)
We present several possibilities offered by nuclear structure, the dynamics of intermediate energy heavy ion collisions and neutron stars to investigate the nuclear matter equation of state (EoS) beyond the ground state. In particular the high density nuclear EoS of asymmetric matter, i.e. the symmetry energy, is discussed.